Análise dos parâmetros de fabricação de elementos de madeira lamelada colada na resposta da qualidade de colagem com base na NBR 7190-6 - Gomes, Nádia Barros [UNESP]; Jardim, Pedro Ignácio Lima Gadêlha; Christoforo, André Luis; Souza, Alexandre Jorge Duarte De [UNESP]; Molina, Júlio Cesar (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2025)
This study aimed to evaluate manufacturing parameters and their impact on the quality of gluing glulam elements. Three stages of research were carried out with Eucalyptus grandis and Pinus elliottii timbers, using different adhesives, analyzing the percentage of delamination and the shear strength of the glue lines. Different bonding pressures were tested with commercial adhesives, quantifying the rupture modes in the bonding zone, different proportions of natural adhesive in the glulam elements and different lamella thicknesses with a two-component polyurethane adhesive. Results indicated that pressures of 0.7 MPa for Pinus and 1.2 MPa for Eucalyptus were in line with the Brazilian standard. Significant differences were observed in the shear strength between Pinus’s outer and inner lamellae. The natural adhesive showed good shear strength, but problems with delamination. The thickness of 3.5 cm showed better bonding quality. The recommendations of NBR 7190-6 proved to be effective in controlling the quality of the bonding of glulam.

Este estudo visou avaliar parâmetros de fabricação e seu impacto na qualidade da colagem de elementos de MLC. Foram realizadas três etapas de pesquisa com madeiras de Eucalipto grandis e Pinus elliottii, usando diferentes adesivos, analisando a porcentagem de delaminação e da resistência ao cisalhamento das linhas de cola. Foram testadas diferentes pressões de colagem com adesivos comerciais, quantificando os modos de ruptura na zona de colagem, diferentes proporções de adesivo natural nos elementos de MLC e diferentes espessuras das lamelas com um adesivo poliuretano bicomponente. Resultados indicaram que pressões de 0,7 MPa para o Pinus e 1,2 MPa para o Eucalipto estavam em conformidade com a norma brasileira. Diferenças significativas foram observadas na resistência ao cisalhamento entre lamelas externas e internas do Pinus. O adesivo natural demonstrou boa resistência ao cisalhamento, mas problemas na delaminação. A espessura de 3,5 cm apresentou melhor qualidade de colagem. As recomendações da NBR 7190-6 se mostraram eficazes no controle da qualidade da colagem de elementos de MLC.
Analysis of the manufacturing parameters of glued laminated timber elements in the response of gluing quality based on NBR 7190-6
Keywords: Glued laminated timber; Gluing quality; Shear at the glue line; Delamination; Gluing pressure; Madeira lamelada colada; Qualidade de colagem; Cisalhamento na linha de cola; Delaminação; Pressão de colagem